EVALUATION PROGRAM FOR CONTROL OF TUBERCULOSIS MULTI DRUG RESISTANT (MDR-TB) WITH STRATEGY DOTS in DISTRICT BANYUMAS - Dhien Setiani; Much Ilham Novalisa Aji Wibowo (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2016)
The emergence of resistance to drugs used to treat TB, and particularly multi-drug-resistant TB (MDR TB), has become a significant public health problem and an obstacle to effective TB control. The resistance is a condition where drugs used to treat TB are not able to kill germs M. tubercolusis. This study aimed to evaluate the success of MDR TB treatment programs in Banyumas include the level of knowledge of TB officer, suitability guidline health care center in Banyumas with national guidelines and describe the factors that affect the implementation of MDR TB program. A cross-sectional descriptive study was conducted from for three months. Quantitative analysis using questionnaires to measure the level of knowledge of TB officers and a checklist for suitability guidline health care center in Banyumas with national guidelines. Qualitative analysis using structured interviews to TB officer or the head of the health care center to explore factors inhibiting and supporting MDR TB control program in the district of Banyumas health centers. The results showed that the level of knowledge officer of MDR was 85.56% in the high category (75% -100%). Level governance suitability MDR TB treatment with national guidelines of 86.94%. Factors that may affect the success of MDR TB program is the economic factor, factor of health workers, patient factors and factors of facilities and infrastructure Key words: TB-MDR drugs used to treat TB, program, evaluation.